2011
DOI: 10.1111/j.1365-2613.2011.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel model of accelerated intimal hyperplasia in the pig iliac artery

Abstract: There is no good animal model of large artery injury-induced intimal hyperplasia (IH). Those available are reproducible, providing only a few layers of proliferating cells or have the disadvantage of the presence of a metallic stent that complicates histology evaluation. This study was designed to develop a new, simple model of accelerated IH based on balloon injury in conjunction with disruption of the Internal Elastic Lamina (IEL) in pig external iliac arteries. Iliac artery injury (n = 24) was performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
3
16
0
2
Order By: Relevance
“…It has been demonstrated in a porcine model that balloon injury in conjunction with disruption of the internal elastic lamina is associated with accelerated intimal hyperplasia vs overdistention without disruption of the internal elastic lamina. 9 This is consistent with our analysis of human peripheral restenotic plaques, which suggested that a breach in the structural integrity of the internal elastic lamina between the tunica media and the tunica intima is associated with increased neointimal proliferation, inflammation, and cellularity compared to de novo atherosclerosis. 10 This correlates with a biological response of cellular proliferation and repair resulting from deep injury leading to restenosis.…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated in a porcine model that balloon injury in conjunction with disruption of the internal elastic lamina is associated with accelerated intimal hyperplasia vs overdistention without disruption of the internal elastic lamina. 9 This is consistent with our analysis of human peripheral restenotic plaques, which suggested that a breach in the structural integrity of the internal elastic lamina between the tunica media and the tunica intima is associated with increased neointimal proliferation, inflammation, and cellularity compared to de novo atherosclerosis. 10 This correlates with a biological response of cellular proliferation and repair resulting from deep injury leading to restenosis.…”
Section: Discussionsupporting
confidence: 91%
“…This was due to the nonlinear stress-stiffening response of arteries where higher expansions increased the level of arterial stresses exponentially. This prediction was verified by comparison to experimental studies which show that the stent expansion diameter is an important predictor of the level of intimal growth [37][38][39][40]. In addition the model predicted a higher restenosis rate for thicker stent struts compared to thinner struts which is consistent with the outcome of many clinical studies [41][42][43][44].…”
Section: In-stent Restenosissupporting
confidence: 70%
“…The pathological examination and the electron microscopy showed that the inner wall of the artificial vessel wall was covered with layer of endothelial cells and vascular smooth cells without any thrombosis. Pig's intimal proliferation may be much more intense than that in human being [ 19 ], which means that the healing capacity may be greater than that in a diseased human aorta, but the difference may not enough to impede we conclude, from these biopsy findings, that the SMSBV has a good biocompatibility.…”
Section: Discussionmentioning
confidence: 97%